PELAKSANAAN PENGADAAN TANAH BAGI PEMBANGUNAN UNTUK KEPENTINGAN UMUM (STUDI DI KOTA MAKASSAR) - Sulastri M (Madani Legal Review, 2019)
The focus of the research is based on facts in the field regarding public land acquisition. Besides wanting to know how the land acquisition process is, it also wants to know the factors that influence land acquisition for the public interest in the city of Makassar. This research is legal research (empirical research) with a legal approach (statute approach). The results of the study indicate that the politics of land law in Indonesia is contained in the LoGA, that the state is not the owner so that the state does not own land. Therefore, the UUPA is not known as eigendom. However, the existence of a state within the scope of the land is only authorized to regulate various issues relating to land in Indonesia, including the authority of land regulation that is increasingly important especially if there are government agencies that need land as the land where development is carried out in the public interest. land to government agencies for development in the public interest, it is deemed necessary to have a legal rule that can be used as a reference in a positive law.